SEJARAH HIJRAH DALAM PERSPEKTIF AL-QUR'AN - Suarni Suarni (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
This paper examines the migration in the context of history. Hijrah is an event that can not be avoided by any creature in the birth of a change. In success, migration is the only way to go. History proves that the implementation of the move is a demand in the carrying direction changes. The changes were done with struggle and sacrifice. In Islam, the Prophet Muhammad is not the first person who did move, but the move has been done by people before. Hijrah is not only done physically but also non-physical.